Drug Interactions Involving 17α‐Ethinylestradiol: Considerations Beyond Cytochrome P450 3A Induction and Inhibition. Issue 6 (24th August 2021) - Rodrigues, A. David
Abstract : It is widely acknowledged that drug‐drug interactions (DDIs) involving estrogen (17α‐ethinylestradiol (EE))‐containing oral contraceptives (OCs) are important. Consequently, sponsors of new molecular entities (NMEs) often conduct clinical studies with priority given to OCs as victims of cytochrome P450 (CYP) 3A (CYP3A) induction and inhibition. Such scenarios are reflected in the US Food and Drug Administration‐issued guidance documentation related to OC DDI studies. Although CYP3A is important, OCs such as EE are metabolized by sulfotransferase 1E1 and UDP‐glucuronosyltransferase (UGT) 1A1, expressed in the gut and liver, and so both can also serve as loci of victim OC DDI. Therefore, for any NME, one should carefully consider its induction and inhibition profile involving CYP3A4/5, UGT1A1, and SULT1E1. As DDI perpetrators, available clinical DDI data indicate that EE‐containing OCs can induce (e.g., UGT1A4 and CYP2A6) and inhibit (CYP1A2 ≥ CYP2C19 > CYP3A4/5 > CYP2C8, CYP2B6, CYP2D6, and CYP2C9) various CYP forms. Although available in vitro CYP inhibition data do not explain such a graded inhibitory effect in vivo, it is hypothesized that EE differentially modulates CYP expression via potent agonism of the estrogen receptor expressed in the gut and liver. From the standpoint of the NME as potential OC DDI victim, therefore, it is important to assess its projected (pre‐phase I) or known therapeutic index and pharmacokinetic profile (fraction absorbed, absolute oral bioavailability, clearance/extraction class, fraction metabolized by CYP1A2, CYP2C19, CYP2A6, and UGT1A4). Such information can enable the prioritization, design, and interpretation of NME‐OC DDI studies.